Bentang Budaya dan Orientasi Spasial di Bali Timur - I Dewa Gede Agung Diasana Putra; I Made Adhika; Anak Agung Ngurah Aritama; Anak Agung Gede Bagus Udayana (Institut Seni Indonesia Denpasar, 2023)
Covid-19 has tremendously impacted global daily life and the built environment, particularly in tourist places' pleasure. Modern architectural practices, such as planning tourist sites, must display new patterns while updating current ones to control contagious diseases efficiently. Polarity is a spiritual concept in Bali that focuses on the impact of nature and geography on traditional Balinese societies. The island's natural environment influences traditional Balinese beliefs and practices on the propriety of specific architectural types and space layouts. According to this theory, the universe was created by colliding two opposed poles. It makes some suggestions for improving the layout of rural villages. This architecture can be seen on the Indonesian island of Bali at several major tourist spots, most notably in the island's eastern area. Despite this, the Covid-19 pandemic underscored the significance of virus prevention in building design, particularly tourist-oriented hotels. Architects, designers, environmentalists, and others in the tourism industry face several challenges while creating and building environmentally sustainable tourist facilities. The study's goal was to see if the traditional architectural principles of eastern Bali could be leveraged to create a tourism facility template that would allow the hospitality industry to meet the demand for new, effective layouts and layout variants. As a result, the villages in eastern Bali that have preserved their old practices have contributed significantly to our understanding of what it means to be a modern human. Professionals can use historical knowledge to build resilient patterns and configurations even when confronted with modern threats, such as viral attacks on famous tourist locations. This study refuted several long-held ideas in light of the Covid -19 results.